Maruina Müller, 1895 (Diptera: Psychodidae): Description of four new species from Brazil, with revised diagnoses for the genus and subgenera - Camico, Jéssica Luna; Cordeiro, Danilo Pacheco; Chagas, Cinthia (Zootaxa, 2019)
Maruina is an aquatic genus of Psychodidae with larvae and pupae adapted for life in flowing water. The genus is restricted to the Western Hemisphere, with the majority of species distributed in the Neotropical region. 39 Maruina species are described, with 11 currently known to occur in Brazil, all recorded from the eastern Biomes of Atlantic forest and Caatinga. Here we describe four new Maruina species collected from Brazil: Maruina (Aculcina) roraimensis sp. nov., Maruina (Maruina) kallyntrona sp. nov. and M. (M.) mystax sp. nov. constitute the first report of Maruina from Amazonia and M. (A.) pila sp. nov. from the southern portion of the Atlantic forest expands the distribution of the genus to Rio Grande do Sul, the southernmost state of Brazil. Type specimens of some described species were also studied. Redescriptions are completed for M. (M.) garota and M. (M.) namorada, and additional characters and figures are presented for M. (A.) duckhousei, M. (M.) barrettoi and M. (M.) jezeki. M. pilosella and M. spinosa are considered nomina dubia. Diagnostic characters for the genus and both subgenera are revised and distribution maps for Maruina species recorded in Brazil are provided. Copyright © 2019 Magnolia Press.
Keywords: Animals; Animals Dispersal; Ecosystem; Larva; Psychodidae; Pupa; Animals Distribution; Animal; Ecosystem; Larva; Psychodidae; Pupa